AN ANALYSIS ENGLISH-INDONESIAN TRANSLATION PROCEDURES USED IN THE WESTERN MOVIE THE CHRISTMAS CHRONICLES - Lucas Abraham Rumbiak Gomes Da Conceicao; I Gusti Nyoman Putra Kamayana (LPPM Universitas Dhyana Pura, 2023)
The aim of this research study is to find out and identify the meaning of a language unitin whole or in part of English to Indonesian translation procedures used in the Western MovieThe Christmas Chronicles, including the effect of the procedures that is used in translating theChristmas Chronicles Movie analysis. The theory of translations procedures used in this studyanalysis was proposed by Peter Newmark. By applying qualitative method, it is intended toidentify the translation procedure and the discussion was presented descriptively. To ensurethe trustworthiness of the research, the data were deeply observed, note taking and nonparticipant discussion of both subtitle English and Indonesian version of the ChristmasChronicles movie. The findings and the discussion show that there are ten out of fourteenprocedures are applied in translating words and phrases in The Christmas Chronicles moviesubtitle from English to Indonesian version. Those are Transference, Naturalization, CulturalEquivalent, Descriptive Equivalent, Through Translation, Recognised Translation, Modulation,Synonymy, Paraphrase and Couplet. The translations method help to understand the sourcelanguage that translate to target language within the same meaning or unchanged from thedifferent procedures.